(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Kachalova T. G. Structural and functional components of a didactic model of forming students’ social competence. The author gives the concept of the social competence as well as defines the component structure of students’ social competence and substantial content of each of its functional components.